S11: What Makes a Whole System Approach to Improving Physical Activity in Children and Young People Effective and Impactful? A Case Study of the JU:MP Intervention (Baltic Journal of Sport and Health Sciences, 2026)
The physical activity and movement behaviours of populations are influenced by complex political, environmental, and social systems rather than just an individual’s ‘intention’ to be active. Whole system approaches that intervene in these complex systems to improve population level physical activity are advocated for by the World Health Organization and the International Society of Physical Activity and Health. However, evidence of their operationalisation and effectiveness is sparse. Since 2018, Sport England (a non-departmental public body under the Department for Culture, Media and Sport) has funded 12 localities across England to pilot whole system, place-based approaches to reduce physical inactivity. One of these localities was Bradford, where an intervention, called JU:MP, aimed to improve physical activity in children aged 5–14 years living in some of the most deprived areas of England.The purpose of this symposium is to share the effects and impacts of the JU:MP intervention and lessons learned about what worked and what did not, with policy makers, practitioners, and researchers. We aim to inspire action and innovation for those planning, developing, implementing, and evaluating whole system physical activity interventions.The symposium will introduce the JU:MP intervention, describing how it is grounded in systems thinking. Four presentations will then showcase a collective of studies conducted to understand the impact and the mechanisms of impact (and context) of the JU:MP whole system approach across different levels of the system, drawing on both effectiveness and process evaluation methodologies. 1) We will examine the findings from a controlled before and after trial which demonstrates the effectiveness of the JU:MP intervention at improving physical activity levels of children aged 5–11 years old, 24 months after JU:MP began. 2) Next, children and families’ experiences of the whole system intervention will be discussed, including critical reflections on their engagement in co-production of the intervention. 3) Our third presentation will explore the impacts, mechanisms, and context of impacts of the JU:MP intervention at the neighbourhood level. 4) The final presentation will provide an explanatory account of the whole system approach to understand how and why the JU:MP whole system intervention worked and could work better.